Практическое применение криогелей; Экологический вестник России; № 1 - Алтунина Л. К. Любовь Константиновна; Манжай В. Н. Владимир Николаевич; Фуфаева М. С. Марина Сергеевна; Филатов Д. А. Дмитрий Александрович (2015, 2015)
Заглавие с экрана